Suitability of AAHPER Fitness Test as a Tool to Measure Physical Fitness of Youth Aged 10 – 17 in Sri Lanka - Somarathna, R.D.A.M.; Jeganenthiran, S.; Sabaananth, S. (Sabaragamuwa University of Sri Lanka, 2017)
Physical fitness is a basic component of total fitness which includes efficiencies, mental and emotional stability and social adaptability. Physical fitness is a positive quality found in people’s age. In a society different strata and groups of people such as young, old, rich and poor; the most important and significant proxy of a society is the youth generation. The AAHPER youth fitness test was devised by American alliance for health, education, and recreation in America. They always concerned with ways to improve the physical fitness. The purpose of this study was to identify suitability of AAHPER youth fitness test to measure fitness of youth aged 10-17 in Sri Lanka. The field based experimental research method was applied to conduct the research with the participation of 1000 girls and boys selected using random sampling method. The study area was throughout the Sri Lanka from various provinces. The data was collected using the AAHPER test batteries which consist with six test items 50 yard run to measure speed, standing broad jump to measure explosive power, shuttle run to measure agility, pull-up for boys and flex arm hang for girls to measure to arm strength, sit up to measure abdominal strength and 600 yard run to measure endurance respectively. Data was analyzed by using SPSS. According to data analysis, following percentile norms were created 5th 10th 15th 20th 25th 30th 35th 40th 45th 50th 55th 60th 65th 70th 75th 80th 85th 90th 95th 100th. When compared to AAHPER test norms, newly assessed norms’ value are more and less. Then using this fitness test can identify the strengths and weaknesses of Sri Lankan youth aged 10-17. This test is suitable for Sri Lankan youth aged 10-17 as a tool to measure their fitness. Further studies are essential to enhance the reliability and validate of the test battery.
Keywords: AAHPER; Physical fitness; Youth age